Wittgenstein o etiki in estetiki: Neizogibnost etike, estetska drža kot Modus srečnega življenja - Žalec, Bojan (Analiza: časopis za kritično misel, 2023)
The article deals with Wittgenstein’s understanding of ethics and aesthetics. The author presents the understanding of early Wittgenstein. He first explains Wittgenstein’s understanding of ethics, and afterwards, his view on the ethical importance of the aesthetic attitude. In this context, he explains in what sense we can talk about ethics as an ineffable (transcendental) condition. The following claim is explained: ethical tautologies are sacrosanct or even sacred, and their violation is tragic; changing the attitude towards the world changes the limits of the world, but not the facts of the world, and the world becomes a different world; ethical »sentences« are formal and absolute; ethics and aesthetics are one; an aesthetic attitude is the heart of a happy life; the ethics of early Wittgenstein is "egocentric" or solipsistic, eudaimonistic, has the characteristics of ethics as an art of life, and is of a personal nature, the ethics of the individual.
Keywords: Wittgenstein; ethics; aesthetics; sanctity of ethical tautologies; tragicness